2010
DOI: 10.1002/hep.23666
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Improves Steroid Sensitivity in Acute Alcoholic Hepatitis

Abstract: Corticosteroid therapy has shown some benefit in severe acute alcoholic hepatitis (AAH); however, this is limited by uncertainty in patient selection and variable clinical response. Theophylline has been shown to ameliorate impaired steroid sensitivity in chronic obstructive pulmonary disease by facilitating corticosteroid-induced silencing of proinflammatory genes. We aimed to explore the mechanistic basis of the variable response to corticosteroid therapy seen in patients with AAH and to address the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…A total of 42 genes are known targets for hepatitis drugs, such as halothane, theophylline and meperidine 50,51 . Only one gene, neuropeptide S receptor 1 (NPSR1), has lost its targeted domain (7tm-1) of halothane in tree shrews owing to the frame-shift mutation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 42 genes are known targets for hepatitis drugs, such as halothane, theophylline and meperidine 50,51 . Only one gene, neuropeptide S receptor 1 (NPSR1), has lost its targeted domain (7tm-1) of halothane in tree shrews owing to the frame-shift mutation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…124 The decision to stop corticosteroids can be based on calculation of the Lille Model after 7 days of treatment; a Lille Model score greater than 0.45 indicates failure to respond to corticosteroid treatment and predicts a 6-month survival rate of less than 25%. 125 Severe acute AH is associated with significant lymphocyte corticosteroid insensitivity, which can be reduced ex vivo by theophylline administration 126 or reagents that block the IL-2 receptor. 127 These drugs might therefore improve the efficacy of corticosteroids in treating AH.…”
Section: Pathogenesismentioning
confidence: 99%
“…(Richardet JP, 1993, Spahr et al, 2001) However, response is observed in only 40–50% patients, whose lymphocytes are sensitive to inhibition of proliferation with corticosteroids. (Kendrick et al, 2010) Further, corticosteroids have potential side effects of such as infections, hyperglycemia, electrolyte disturbance, and weight gain. Of these, infection, especially fungal infections, is most relevant in AH patients.…”
Section: Resultsmentioning
confidence: 99%